2008
DOI: 10.1111/j.1447-0349.2008.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Former patients' experience of psychiatric care: A qualitative investigation

Abstract: In this study, 10 former patients' experiences of hospitalization are described using a qualitative approach. The informant group consisted of three men and seven women with different diagnoses and each with his or her individual experience of life as an inpatient. The aim of this study was to extend our understanding of former psychiatric inpatients' experience their time of admission to a psychiatric inpatients unit. Data were collected and analysed using a content analysis approach. From the former patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 28 publications
3
104
0
Order By: Relevance
“…The women became frustrated, but adapted to it passively because they had no other choice. Similar results were reported by Lilja and Hellzén (2008), who found that patients in psychiatric wards described spending time without events as being kept in storage and found ways of coping with daily life by themselves with things like sleeping, playing games or just adapting. Radcliff and Smith (2007) found that in an acute psychiatric ward, patients spent 84% of their time socially disengaged and almost half of that time alone in their bedrooms.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The women became frustrated, but adapted to it passively because they had no other choice. Similar results were reported by Lilja and Hellzén (2008), who found that patients in psychiatric wards described spending time without events as being kept in storage and found ways of coping with daily life by themselves with things like sleeping, playing games or just adapting. Radcliff and Smith (2007) found that in an acute psychiatric ward, patients spent 84% of their time socially disengaged and almost half of that time alone in their bedrooms.…”
Section: Discussionsupporting
confidence: 86%
“…Shattell, Andes, and Thomas (2008) found that patients' time passed slowly and they simply waited for the next meeting with doctors, nurses, family or just anybody. Lilja and Hellzén (2008) and Borge and Fagermoen (2008) reported that adapting and being passive could be considered a risk because it could entirely overwhelm the patient.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in other research, the findings of this study reflect the mental health patients' desire to be respected and treated as equal human beings (Johansson & Eklund, 2003;Koivisto et al 2004;Lilja & Hellzén, 2008;Schröder et al, 2006;Vatne & Hoem, 2007). Interestingly, Hem and Heggen (2003) found that psychiatric nurses reported difficult role conflicts when faced with the contradictory demands of being "professional" and being "human."…”
Section: Discussionsupporting
confidence: 78%
“…Patients highlight the importance of the therapeutic relationship in providing a safe and therapeutic milieu (14)(15)(16). Even if mental disorders usually have their onset in childhood or adolescence (17), there are only a few studies that examine the view of young adult patients (18,19).…”
Section: Introductionmentioning
confidence: 99%